Chandra ACIS Survey of M33 (ChASeM33): A first look - Plucinsky, Paul P.; Williams, Benjamin; Long, Knox S.; Gaetz, Terrance J.; Sasaki, Manami; Pietsch, Wolfgang; Tuellmann, Ralph; Smith, Randall K.; Blair, William P.; Helfand, David; Hughes, John P.; Winkler, P. Frank; et al. (Astrophysical Journal Supplement Series, 2008)
We present an overview of the Chandra ACIS Survey of M33 (ChASeM33): A Deep Survey of the Nearest Face-on Spiral Galaxy. The 1.4Ms survey covers the galaxy out to R approximate to 180( approximate to 4 kpc). These data provide the most intensive, high spatial resolution assessment of the X-ray source populations available for the confused inner regions of M33. Mosaic images of the ChASeM33 observations show several hundred individual X-ray sources as well as soft diffuse emission from the hot interstellar medium. Bright, extended emission surrounds the nucleus and is also seen from the giant H II regions NGC 604 and IC 131. Fainter extended emission and numerous individual sources appear to trace the inner spiral structure. The initial source catalog, arising from similar to 2/3 of the expected survey data, includes 394 sources significant at the 3 sigma confidence level or greater, down to a limiting luminosity ( absorbed) of similar to 1: 6; 1035 ergs s(-1) (0.35-8.0 keV). The hardness ratios of the sources separate those with soft, thermal spectra such as supernova remnants from those with hard, nonthermal spectra such as X-ray binaries and background active galactic nuclei. Emission extended beyond the Chandra point-spread function is evident in 23 of the 394 sources. Cross-correlation of the ChASeM33 sources against previous catalogs of X-ray sources in M33 results in matches for the vast majority of the brighter sources and shows 28 ChASeM33 sources within 1000 of supernova remnants identified by prior optical and radio searches. This brings the total number of such associations to 31 out of 100 known supernova remnants in M33.
Keywords: galaxies : individual (M33); supernova remnants; X-rays : galaxies